Menggerakkan Perubahan: Mahasiswa Sebagai Agen Pendidikan Dalam Meningkatkan Kualitas Pendidikan Melalui Kegiatan Kkn Di Desa Rejeki Kecamatan Palolo Kabupaten Sigi - rauf, abdur; Aditya Pratama, Moh; Azmita, Fajria; Umairah, Nurul; Azzahra, Fatimah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
KKN activities for Batch LXIV of Muhammadiyah University of Palu at Post XIV Palolo will take place from 24 July to 2 September 2023. The preparation of the work program in this activity was based on the observation method, which resulted in a work program that was successfully implemented. One of the work programs implemented is improving the quality of education through teaching and guidance. Students are directly involved as facilitators in the tutoring program. All work programs were successfully implemented well, on time and in line with expectations. This activity makes a positive contribution to the community in Rejeki village, Palolo District, Sigi Regency